Immunomodulatory Effects of the Neuropeptide Pituitary Adenylate Cyclase-Activating Polypeptide in Acute Toxoplasmosis - Figueiredo, Caio Andreeta; Düsedau, Henning Peter; Steffen, Johannes; Gupta, Nishith; Dunay, Miklos Pal; Toth, Gabor K.; Reglodi, Dora; Heimesaat, Markus M.; Dunay, Ildiko Rita (Frontiers in Cellular and Infection Microbiology, 2019)
Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) is an endogenous neuropeptide with distinct functions including the regulation of inflammatory processes. PACAP is able to modify the immune response by directly regulating macrophages and monocytes inhibiting the production of inflammatory cytokines, chemokines and free radicals. Here, we analyzed the effect of exogenous PACAP on peripheral immune cell subsets upon acute infection with the parasite Toxoplasma gondii (T. gondii). PACAP administration was followed by diminished innate immune cell recruitment to the peritoneal cavity of T. gondii-infected mice. PACAP did not directly interfere with parasite replication, instead, indirectly reduced parasite burden in mononuclear cell populations by enhancing their phagocytic capacity. Although proinflammatory cytokine levels were attenuated in the periphery upon PACAP treatment, interleukin (IL)-10 and Transforming growth factor beta (TGF-β) remained stable. While PACAP modulated VPAC1 and VPAC2 receptors in immune cells upon binding, it also increased their expression of brain-derived neurotrophic factor (BDNF). In addition, the expression of p75 neurotrophin receptor (p75NTR) on Ly6Chi inflammatory monocytes was diminished upon PACAP administration. Our findings highlight the immunomodulatory effect of PACAP on peripheral immune cell subsets during acute Toxoplasmosis, providing new insights about host-pathogen interaction and the effects of neuropeptides during inflammation.